Importance of multidisciplinary collaboration for smooth kidney transplantation in HIV-infected patients with chronic kidney disease: a case report - Tetsuya Abe; Daisuke Ishii; Yuki Imura; Ayano Noguchi; Kazuki Kitajima; Yasuo Takeuchi; Tatsuhiko Wada; Kazunari Yoshida (Renal Replacement Therapy, 2022)
Abstract Background Antiretroviral therapy (ART) has reduced mortality caused by AIDS resulting from HIV infection. Meanwhile, the prevalence of chronic kidney disease, a chronic HIV complication, is increasing. Antiretroviral therapy has improved the life expectancy of HIV-infected kidney transplant recipients. In Japan, discrimination and prejudice against HIV persist, and few kidney transplants are performed. We report three cases in which kidney transplantation was smoothly performed with multidisciplinary collaboration. Case presentation The first case involved a 29-year-old male urgently hospitalized due to severe kidney dysfunction, diagnosed with HIV-associated nephropathy (HIVAN), and placed on maintenance dialysis. The patient was administered oral lamivudine, abacavir, and raltegravir as ART and underwent blood group-matched living donor kidney transplantation at age 32. The second case involved a 49-year-old male diagnosed as HIV-positive at age 33 and placed on maintenance dialysis for HIVAN at age 47. Darunavir, ritonavir, and dolutegravir (DTG) were initially administered. However, the ART was switched to rilpivirine (RPV) and DTG prior to kidney transplantation because of potential ART interactions with calcineurin inhibitors. The patient underwent blood group-matched living donor kidney transplantation. The third case involved a 41-year-old male diagnosed as HIV-positive at 23 years old and treated with RPV and DTG. Due to autosomal dominant polycystic kidney disease (ADPKD), his kidney function gradually worsened, and he was started on hemodialysis. He underwent hemodialysis, followed by blood type-matched living donor kidney transplantation. In all cases, transplant physicians, nephrologists, infectious disease physicians, hepatologists, nurses, pharmacists, nutritionists, and clinical psychologists collaborated to discuss and share medical problems and sociopsychological backgrounds of the patients. There was no rejection, CD4+ lymphocyte counts were maintained, and there was no increase in viral load post-surgery. Information sharing among various departments has continued post-surgery, kidney function has improved, and no increase in viral load has been identified on follow-up. Conclusions Kidney transplantation is the kidney replacement therapy of choice for HIV-infected patients with CKD. Specialized support is required for kidney transplantation, including coordinating immunosuppressive therapy to avoid rejection, learning about drug interactions, and providing sociopsychological support. Multidisciplinary collaboration is important to ensure safe and smooth kidney transplantation care for HIV-infected patients.